Treatment of Dysphagia in Parkinson’s Disease: A Systematic Review - López-Liria, Remedios (Int J Environ Res Public Health, 2020)
The incidence of oropharyngeal dysphagia in Parkinson’s disease (PD) is very high. It is necessary to search for effective therapies that could prevent pneumonia. Previous results should be interpreted cautiously as there is a lack of evidence to support the use of compensatory or rehabilitative approaches to dysphagia. We reviewed the scientific literature to describe the treatments of dysphagia in PD. A systematic review was performed in PubMed, Scopus, Elsevier, and Medline according to PRISMA standards in 2018. The articles that did not mention dysphagia secondary to PD or used surgical treatment were excluded. Eleven articles met the criteria with information from 402 patients. The review relates to different protocols, such as training in expiratory muscle strength, postural techniques, oral motor exercises, video-assisted swallowing therapy, surface electrical stimulation, thermal stimulation, touch, compensatory interventions, training regime for swallowing, neuromuscular electrical stimulation, Lee Silverman voice treatment, swallow maneuver, airway protection, and postural compensation maneuvers. This review identifies the rationing interventions in each trial, if they are efficient and equitable. Several rehabilitative therapies have been successful. An improvement was seen in the degenerative function (coordination, speed, and volume), quality of life, and social relationships of people with PD. Further investigations concerning the clinical applicability of these therapies based on well-designed randomized controlled studies are needed. Larger patient populations need to be recruited to evaluate the effectiveness, long-term effects, and new treatment techniques.